Monday

November 24, 2014

November 24, 2014

Posted by **Lilly** on Sunday, October 19, 2008 at 3:33pm.

a=b

a + [c + (-c)] = b + [c + (-c)]

Also, would the property expressed in -a=-b be the substitution property of equality?

**Answer this Question**

**Related Questions**

Math Properties - What property is expressed in the equality b + (-b) = 0?

Math Help - I'm not really sure on how to prove statements are right with ...

math - suppose 6% of 8000 people polled regarding election expressed no opinions...

Geometry HELP!! - I need help with my geometry hw, i need to now wat the ...

maths - The sum of odd squares can be expressed as 1^2+3^2+5^2+…+(2n-1)^2=An^3+...

Math - which of the following properties hold for subtraction of whole numbers? ...

math - The sum of squares formula is given by 1^2+2^2+3^2+…+n^2=n(n+1)(2n+1)/6. ...

English expression - 'Glad to meet you.' is expressed as 'Nice to meet you...

math - which of the following percents can also be expressed as a mixed number? ...

HELP MATH - What property is demonstrated by the following? y = 3x + 7 and x = 3...